Closing the communication gap an effective method for achieving desired results - Harrington, H. J. (Productivity Press, 2014)
Annotation
Includes bibliographical references. - Print version record
Keywords: Communicative competence; Interpersonal communication; Communication; Communication interpersonnelle; Information; BUSINESS & ECONOMICS; General; BUSINESS & ECONOMICS; Quality Control; PSYCHOLOGY; Social Psychology